2017
DOI: 10.1002/aic.15942
|View full text |Cite
|
Sign up to set email alerts
|

La‐hexaaluminate for synthesis gas generation by Chemical Looping Partial Oxidation of Methane Using CO2 as Sole Oxidant

Abstract: in Wiley Online Library (wileyonlinelibrary.com)Chemical looping partial oxidation of methane using a sole CO 2 oxidant (CL-POM-CO 2 ) is an emerging technology for synthesis gas generation and CO 2 utilization, which is highly dependent on an oxygen carrier (OC). In this work, Fe-substituted La-hexaaluminate as the OC was found to exhibit good reactivity and stability during 50 periodic CH 4 / CO 2 redox cycles due to the formation of magnetoplumbite La-hexaaluminate structure with the introduction of La. Dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…There are mainly two options: one is to enhance the reactivity of V 2 O 3 and the other is activation of CH 4 molecules. It was reported that elemental doping may result in synergetic effect on lattice oxygen mobility, melting point, and so forth . Additives such as TiO 2 , ZrO 2 , Al 2 O 3 , K 2 O, La 2 O 3 , and Ce 2 O 3 were tested, little or even negative effect was observed among these composite materials, except that SiO 2 addition showed an positive result.…”
Section: Resultsmentioning
confidence: 99%
“…There are mainly two options: one is to enhance the reactivity of V 2 O 3 and the other is activation of CH 4 molecules. It was reported that elemental doping may result in synergetic effect on lattice oxygen mobility, melting point, and so forth . Additives such as TiO 2 , ZrO 2 , Al 2 O 3 , K 2 O, La 2 O 3 , and Ce 2 O 3 were tested, little or even negative effect was observed among these composite materials, except that SiO 2 addition showed an positive result.…”
Section: Resultsmentioning
confidence: 99%
“…Its application for CLR of CH 4 , however, is a relatively new topic which have been studied by Wang’ research group. They firstly examined the feasibility of LaFe 3 Al 9 O 19 (LF3A) for CLDR and found that it exhibited good reactivity and stability during 50 periodic CH 4 /CO 2 redox cycles for synthesis gas formation and CO 2 conversion [59] . Interestingly, magnetoplumbite (MP) La‐hexaaluminate structure was maintained even after deeper reduction, which was quite different from the OCs reported previously where phase transformation usually occurred.…”
Section: Oxygen Carriersmentioning
confidence: 93%
“…Then they further identified that oxygen coordinated with Fe 3+ in octahedral Al(3) sites (O 6 −Fe 3+ (Oh)) was highly active for the total oxidation while that in trigonal bipyramidal Al(5) sites (O 5 −Fe 3+ (Tr)) and tetrahedral Al(2) sites (O 4 −Fe 3+ (Th)) selectively oxidized CH 4 to synthesis gas. Unlike the regeneration of O 2 for O 6 −Fe 3+ (Oh), CO 2 oxidation only selectively recovered O 5 −Fe 3+ (Tr) and O 4 −Fe 3+ (Th), which indicated its more favor for improving synthesis gas selectivity as oxidants than O 2 /air [59] . Based on these results, BaFe 3 Al 9 O 19 (BF 3 A) with decreased active sites of Fe 3+ in Al(1), Al(2), and Al(3) sites (Fe 1 ,Fe 2 and Fe 3 ) for CO 2 and increased those of Fe 2+ for CO formation was designed by shortening the regeneration period, which achieved significant enhancement of CO selectivity from 58 % to 83 % [58] .…”
Section: Oxygen Carriersmentioning
confidence: 97%
“…Nevertheless, the reduced Ni dramatically promotes methane decomposition, which leads to serious carbon deposition and deactivation of the redox catalysts [18][19][20]. Fe-based oxides are much cheaper than nickel oxides and nontoxic; thus, they have been studied extensively as alternative oxygen carriers [21][22][23][24]. However, owing to their lower reactivity toward methane than nickel oxides and the severe sintering under high reaction temperatures, a support material such as Al2O3 and SiO2 is required, which overcomes these drawbacks by increasing the dispersion of oxygen carriers and minimizing the crystalline size of the iron oxides [5,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%